Integrated aquaculture-agriculture: Fish culture and plant crops module for arid areas - Elewa, Ahmed; Nasr-Allah, Ahmed (WorldFish, 2023)
This guide explains the integration between fish culture and conventional crop agriculture and discusses how farmers can maximize benefits from using these resources. The main concept for any system of integration is that the outputs of one organism or system function as a source of inputs for another organism or system. For fish farmers, this concept applies to the relationship between fish and crops, as theoutputs of the fish can be a rich source of nutrients for crops.